Epibionts on water Flea Moina macrocopa (STRAUS) and Brine Shrimp ( Artemia sp.) - Bawpit Charubhun (Agriculture and Natural Resources, 1990)
Epibionts on water flea Moina macrocopa (STRAUS ) and brine shrimp, Artemia sp. in Bangkok was investigated from October, 1988 through September, 1989. The mycelium of unidentified fungus, sporangium of Fusarium sp., protozoa, Epistylis sp. and rotifer, Brachionus rubens were found on the body surface and appendages of water fleas. Filamentous bacteria and prtozoa, Zoothamnium sp. were found on egg shell, nauplius larva and adult of brine shrimp. Infested brine shrimp with bacteria and protozoa were found more frequently on egg shell and adult than they were found in the nauplius larva. The presence of Zoothamnium sp., Epistylis sp. and filamentous bacteria are important as they are known to cause extensively mortality in post larva of shrimps.